Association of Shift Working with Mental Emotional Disorder in Oil and Gas Workers with Cardiovascular Risk: A Cross-Sectional Study - Chandra Halim; Dewi S. Soemarko; Ade Mutiara; Nuri P. Adi; Marsen Isbayuputra (The Indonesian Journal of Community and Occupational Medicine, 2026)
Background: Offshore oil and gas workers face long shifts, unhealthy diets, and low activity, leading to a high cardiovascular disease burden.These workers were also reported to have high rates of anxiety and mental distress. Understanding the association between these healthchallenges will help develop better wellness initiatives and improved emergency mitigation plans.Objective: This study aimed to investigate the association of cardiovascular risks and occupational factors with the prevalence of mentalemotional disorder among workers in an offshore oil and gas company.Method: This analytical observational cross-sectional study was conducted in an offshore oil and gas population, using two secondary datasources. Cardiovascular risks were measured using 2025 annual health checkup results, while the MED (mental emotional disorder) wasscreened using the Indonesian-validated SRQ-20.Result: Among 126 subjects, 16.7% experienced mental emotional disorder symptoms, and 73% had abnormal blood pressure. However,none of the cardiovascular risks were significantly associated with mental emotional disorder. On the contrary, shift work was found to bethe determinant factor associated with mental emotional disorder in this study (p = 0.007, aOR = 0.17)Conclusion: Non-shift work is a significant independent factor associated with MED. This highlights that psychosocial factors play anessential role in workers’ well-being.